Violence and Power in Stories about the War by Carmen De Burgos - Rigoni, Mirtha Laura (Revista Melibea, 2025)
Journalist and prolific writer, Carmen de Burgos (Almería, 1867- Madrid, 1932), also known by one of her pseudonyms, “Colombine”, addressed diverse genres such as the chronicle, the column and the opinion article, the essay, the information manual (about cooking, health or home economics, for example), in addition to the novel. Heir to nineteenth-century realism and perhaps influenced by the journalistic work she carried out, she worked in her fiction with materials from the reality of her time based on careful observation, creating characters immersed in conflicts not unrelated to her own concerns. We are interested in investigating in her short novels about war (Melilla and the First World War) how the role of women, who oscillates between submission and empowerment, is configured in a scenario of violence. The author also tried to fight some battles not framed in war conflicts in defense of women's rights, which is reflected in her literature: it is again the vulnerability of bodies and the exercise of power that is at stake in her fictional stories, although the scenarios and problems are different.